Bounds on Minimum Distance for Linear Codes over GF. - Daskalov, Rumen N. (Applicable algebra in engineering, communication and computing.)
Let [n, k, d; q]-codes be linear codes of length n, dimension k and minimum Hamming distance d over GF(q). Let d 5(n, k) be the maximum possible minimum Hamming distance of a linear [n, k, d; 5]-code for given values of n and k. In this paper, forty four new linear codes over GF(5) are constructed and a table of d 5(n, k) k≤ 8, n≤ 100 is presented.